ANALISIS ELASTISITAS HARGA KOPI ARABIKA DAN ROBUSTA SERTA IMPLIKASINYA TERHADAP PENDAPATAN PETANI (STUDI KASUS: KECAMATAN SAMARANG, KABUPATEN GARUT) - Asep Abdul Manap; Salma Aaliyah; Yusuf Prayoga Arasid; Ira Murwenie (Jurnal Riset Multidisiplin Edukasi, 2025)
Fluctuations in domestic and global coffee prices affect the income of farmers in production centers such as Samarang District, Garut. This study analyzes the effect of Arabica and Robusta coffee prices on farmers' income and calculates the elasticity of supply. Using quantitative methods with descriptive and associative analysis, data were collected through interviews, observations, and documentation of transactions at one local coffee producer, with 30 farmers as a purposive sample. Simple linear regression shows that Arabica and Robusta prices have a significant effect on income (significance 0.000), with R Square of 0.950 and 0.957, respectively. The elasticity of supply for Arabica is 81.93 and for Robusta is 23.78, indicating that both are highly elastic, influenced by variations in production due to climate, season, and agroclimatic conditions. These findings confirm the importance of price fluctuations in determining farmers' income, thus requiring price stabilization strategies and strengthening of trade practices to improve the welfare of coffee farmers in Semarang.